Factor Affecting Sharecropping System in East Java: an Islamic Prespective Analysis (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2021)
This research aims to understand the relationship between socioeconomic factors, production, transparency with religiosity. The effects of socio-economic factors, production, transparency, and religiosity on the sharecropping contract system. Design/methodology/approach: The author has administered a survey to 800 respondents. The respondents were asked to give their responses based on a five-point Likert scale. The data has been tested with SEM to show the relationship between the various factors. Finding: SEM results show that H1 is not supported while H2, H3, H4, H5, H6, and H7 are supported. Findings show that religiosity impacts the sharecropping system while the interaction between religiosity and transparency on the sharecropping system is significantly negative. Therefore, the current sharecropping contract system in East Java does not operate following Islamic values.